Alternative Splicing of TaGS3 Differentially Regulates Grain Weight and Size in Bread Wheat - Xiaoli Ren (MDPI AG, 2021)
The heterotrimeric G-protein mediates growth and development by perceiving and transmitting signals in multiple organisms. Alternative splicing (AS), a vital process for regulating gene expression at the post-transcriptional level, plays a significant role in plant adaptation and evolution. Here, we identified five splicing variants of Gγ subunit gene TaGS3 (TaGS3.1 to TaGS3.5), which showed expression divergence during wheat polyploidization, and differential function in grain weight and size determination. TaGS3.1 overexpression significantly reduced grain weight by 5.89% and grain length by 5.04%, while TaGS3.2–3.4 overexpression did not significantly alter grain size compared to wild type. Overexpressing TaGS3.5 significantly increased the grain weight by 5.70% and grain length by 4.30%. Biochemical assays revealed that TaGS3 isoforms (TaGS3.1–3.4) with an intact OSR domain interact with WGB1 to form active Gβγ heterodimers that further interact with WGA1 to form inactive Gαβγ heterotrimers. Truncated isoforms TaGS3.2–3.4 , which lack the C-terminal Cys-rich region but have enhanced binding affinity to WGB1, antagonistically compete with TaGS3.1 to bind WGB1, while TaGS3.5 with an incomplete OSR domain does not interact with WGB1. Taking these observations together, we proposed that TaGS3 differentially regulates grain size via AS, providing a strategy by which the grain size is fine-tuned and regulated at the post-transcriptional level.